The clinical research office of the endourological society audit committee - Preminger, Glenn M.; Alken, Peter; Habuchi, Tomonori; Wijkstra, Hessel; Skolarikos, Andreas; Yin, Chan-Jun (Journal of endourology, 2011)
The Clinical Research Office of the Endourological Society (CROES) conducts large-scale, international, multicenter clinical trials in the field of endourology. One of the major challenges that these trials pose is to ensure that data collected remotely and online within a very short time frame are valid and reliable. This editorial describes a formal process for auditing the data by the CROES Audit Committee. The audit process presented is largely based on an automatic scoring system, which takes into consideration several parameters to determine the quality of the data and of the participating institution. This process is dynamic in nature and offers live monitoring of both patient data and study centers.